Perceptions of Faculty Members on the Role of the Translation Curriculum in Developing Intercultural Communication Competence among EFL Students at King Khalid University - Alhaj, Ali Albashir Mohammed; Alwadai, Mesfer Ahmed Mesfer (Technium Social Sciences Journal, 2023)
In the current world, intercultural communication competence brings out the capabilities that allow people to carry out effective communications in cross-cultural surroundings and recount diverse cultural attitudes. A closer look at the relationship between intercultural communication and translation indicates that translation and intercultural communication are explicitly interrelated and can be mutually realized. The current research paper mainly purports to extrapolate the perceptions of faculty members on the role of the translation curriculum in developing intercultural communication competence among EFL students at King Khalid University. The key significance of this study is how faculty members of translation perceived the role played by the translation curriculum in enhancing intercultural communication and cultural dialogue among EFL students. The main questions of this study are: (1) What are the general perspectives of faculty members concerning the role played by the translation curriculum in developing ICC among university students of translation? (2) To what extent does the translation curriculum affect translation students' ICC as an integral component of linguistic competence as perceived by faculty members of translation? Moreover, to accomplish the objectives of the study, the two researchers utilized a descriptive research method. Information gathering was collected by dint of using a questionnaire of fourteen items based on a five-point Likert scale. Some English-language staff members were randomly selected from King Khalid University. The study's results revealed that most staff members showed positive perceptions towards the role of the translation curriculum because it helped their translation students understand more about their culture than other cultures. The findings of the study also showed that most staff members perceived the translation curriculum can make their translation students have an aspiration to learn more crucial knowledge and capabilities to communicate effectively in intercultural meets. Premised on the findings, the study will offer some recommendations and implications on the role of translation curriculum in developing intercultural communication competence among EFL university students in general and at King Khalid University in particular.